As trabalhadoras da categoria das indústrias metalúrgicas, mecânicas e de material elétrico de Campinas e região/SP e o “novo sindicalismo” (1984 –1988) - Silva, Gabriela Costa da (2020)
The present paper aims to point out the main claims of the workwomen during the “New Syndicalism” and summarize the participation of this group in the SMCR between 1984 and 1988. In order to do that, it is presented a discussion on the implications of the condition of “being a woman, being a workwoman” in the participation of social movements as well as the perspective of the research about the moment of Brazilian syndicalism known as “New Syndicalism”. In that context, the third largest Trade Union of this workers category in the state of São Paulo, the SMCR, inserted at a relevant economical and industrial Brazilian spot, following the riots of ABC Paulista, it is present in the famous claims for better salary and work conditions that took place very important demands of the 1980s. Therefore, aiming to respond to the questions of this study and lower the number of historical gaps, mainly about the workwomen history during the Brazilian re-democratization process, the reports made and distributed by SMCR between 1984 and 1988, altogether with the oral testimonies collected with the workers of that time, were used as the basis for the research. . As a conclusion, it can be pointed that the workwomen were present at the big mobilizations that took place in the Campinas area. Moreover, this situation was a result of the joining of the feminist social movements and, specifically in the Campinas area, directly related to the Catholic Left and the Union Opposition as well as the actual Union Movement. This work is linked to the activities developed in the Research Line “Culture, Migrations and Work”, of the Postgraduate Program in History at the Federal University of Santa Maria, and was funded by the Capes Demanda Social Scholarship.